Pengaruh Penggunaan Model Pembelajaran Time Token Terhadap Peningkatan Kemampuan Komunikasi Peserta Didik - Dentin Marimmas; Rita Zahara; Bella Anantha Sritumini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2018)
This research is motivated by the problem of increasing communication skills of low students, especially on professional ethics subjects. The purpose of this study is to obtain information about the Time Token Model. In the subject of professional ethics in improving the communication skills of students. The research design used in this study is the Quasy experiment Nonequivalent Control Group Design. The increase is seen from each indicator of student learning outcomes which includes verbal and nonverbal communication skills. In conclusion, from the hypothesis which states based on the testing of the information obtained, it can be concluded that there are differences in learning outcomes when the Time Token model is applied. Based on the evidence that the hypothesis which reads